Architectural Influences In VR: Digital Environments Impact For Enhanced Motivation In Static Cycling - Wiguna, Made Mas Surya; Prabawa, Made Suryanatha; Wicaksana, Gde Bagus Andika (Jurnal Info Sains : Informatika dan Sains, 2024)
The incorporation of Virtual Reality (VR) into stationary cycling routines presents a promising strategy for boosting exercise motivation, particularly through the utilization of good digital architectural environments initially created for therapeutic objectives. The primary objective of this research is to investigate the impact of VR's digital architecture design on motivation levels during physical activity. A repurposed VR system was utilized in this investigation, showcasing digitally simulated natural surroundings in a program involving 18 participants. These individuals underwent evaluations utilizing the Behavioral Regulation in Exercise Questionnaire (BREQ) alongside initial surveys concerning exercise behaviors and familiarity with digital gaming. Findings demonstrated a significant enhancement in motivation, achieving an estimated success rate of 83.33% within the participant group, especially evident among those with previous gaming exposure. Nevertheless, external motivational elements such as perceived duty and social pressure also surfaced as noteworthy considerations. Despite these concerns, feedback was predominantly positive, affirming the effectiveness of the VR system in elevating exercise motivation. The results propose substantial ramifications for the expansion of VR applications in exercise programs, promoting the need for more extensive research to evaluate long-term effects and broaden participant demographics to authenticate and broaden these findings. This investigation underscores the potential of VR in rendering exercise more interactive and flexible, proposing a revolutionary approach to improving physical activity participation.